Radio in the disintegration era: Migration of the conventional radio in Malaysia - Intan Soliha Ibrahim; Juliana Abdul Wahab (Taylor’s University Sdn Bhd, 2021)
Radio is often regarded as one of the important mediums to reach the masses. In the last decade or so, the radio industry has faced unprecedented challenges with new developments in broadcast technology where digital media and digital content have become popular amongst the public. In the past, the development of radio lagged compared to television and other forms of new media in reaching out to the mass listeners. However, digitalisation and convergence in the radio industry have changed the way listeners consume radio content. Migration to digital technology has made access to radio more convenient than ever. We can now tune to radio from various platforms such as smartphones, radio apps, online radio, and television to enjoy music and obtain the latest information about the world around us. This article aims to highlight the issues and challenges faced by the conventional radio in the disintegration era, specifically looking at the development of the radio industry in Malaysia. The lack of academic work about radio within the local context has left a void in understanding the latest developments of the radio industry. This study used a qualitative approach by conducting in-depth interviews with key market players to examine the survival of radio in the disintegration era. The findings show that the migration from conventional to digital radio is gradual and uncertain. Government, industry players and listeners play vital roles in the development and future of digital radio in this era.